Effect of Non-Thermal Alkaline (Lime) Soaking on Amino Acid Profile of Maize (Zea mays L.): A Modified Nixtamalization Approach - Asnawi Baso; Rimbawan Rimbawan; Lilik Kustiyah (Media Publikasi Cendekia Indonesia, 2026)
Maize (Zea mays L.) is one of the major sources of dietary energy and protein for humans; however, its protein quality is limited due to deficiencies in essential amino acids, particularly lysine and tryptophan. Traditional lime-based processing (nixtamalization) has long been applied in Mexico for tortilla production and shares similarities with local maize-processing practices on Buton Island, Indonesia, which also utilize lime solutions. This study applied a modified nixtamalization approach, in which maize kernels were soaked in a lime solution under non-thermal conditions, followed by water-based heating. The objective of this study was to evaluate the effects of the treatment on the amino acid profile and amino acid scores of maize protein, with water soaking used as the control. Amino acid profiles were analyzed using high-performance liquid chromatography (HPLC), and amino acid scores were calculated based on FAO/WHO reference patterns for children aged ≥3 years and adults. The results showed that the relative ratios of lysine and tryptophan were higher than those of the control (1.39 and 1.09, respectively), whereas arginine exhibited a markedly lower ratio (0.19). This non-thermal alkaline treatment reflects changes in the amino acid profile of maize protein, although it was accompanied by a reduction in total protein content. However, the implications of these changes in the amino acid composition for the biological quality of protein still require further verification through digestibility-based measurements. This lime-based approach inspired by local practices may represent an alternative processing strategy for modulating the amino acid profile of maize, with indications of alterations in essential amino acid composition and increased amino acid scores